A chemometrics approach comparing characteristics and free radical scavenging capacity of flax (Linum usitatissimum L.) oils obtained from seeds and cakes with different extraction methods. (15th March 2021) - Zhang, Youfeng; Zhou, Yang; Song, Zhihua; Jin, Jun; Tang, Junjun; Wang, Xingguo; Huang, Jianhua; Jin, Qingzhe
Abstract: BACKGROUND: Flax oil, a nutritive vegetable oil, is a rich natural source of the essential C18:3 α‐linolenic acid and trace nutrients (tocopherol, phytosterol, polyphenol, flavonoid, etc.). In most small‐ and medium‐sized facilities, the oil content in pressed cake is as high as 10%, which is not fully extracted and utilized. These cannot be neglected since they account for a considerable proportion. Characteristics and free radical scavenging capacity of flax ( Linum usitatissimum L.) oil obtained from seeds and cakes with different extraction methods – cold‐pressing, hot‐pressing (120 and 160 °C) and solvent extraction (oil extracted with solvent from flaxseed, cold‐pressed cake, and hot‐pressed cake) – were evaluated and analyzed using chemometrics methods. RESULTS: The composition of C18:3 α‐linolenic acid of flax oil was not affected by the extraction methods in this work. Flax oils extracted with solvent from pressed cakes had lower content of bioactive minor components (tocopherols and phytosterols) compared with pressed and solvent‐extracted seed oils. The former also showed poorer oxidative stability and free radical scavenging capacity (polar fraction) when compared with the latter. Flax oils could be distinguished with principal component analysis and hierarchical cluster analysis. Tocopherols and phytosterols exhibited significant contributions to the antioxidant capacity of flax oils via correlation analysis and multiple linear regression analysis. CONCLUSION: Tocopherols and phytosterols were appropriate and potent indicators for evaluating the antioxidant capacity of flax oil. Results have important implications for the industrial production and nutritional value of flax oil, especially for flax oils from the cakes after pressing. © 2021 Society of Chemical Industry.